Forms of Trade Union Disciplinary Sanctions: A Comparative Study - Kadhim Kathe Al-Mushailawi, Researcher. Saud; Abdul Abbas Naeem, Assist. Prof. Dr. Ali (Basra studies journal, 2024)
The disciplinary system is one of the most important means of self-regulation in professional unions, given the significant authority vested in disciplinary committees or councils. This authority relates to the ability to assess errors and recommend appropriate sanctions, aiming to evaluate the behavior of professional union members, achieve discipline and compliance among them, and ensure the fulfillment of these goals. Professional unions have been granted disciplinary authority to monitor and guide committed members and to punish those who violate professional principles. The legislator has specified disciplinary sanctions in a non-exhaustive manner and arranged them in ascending order according to severity. Disciplinary committees and councils are granted discretionary power to impose sanctions deemed appropriate according to the severity of the violation, in case it is proven to have been committed by the union member. Despite some variations in disciplinary systems, structures, and powers of disciplinary councils, and procedures for imposing disciplinary sanctions from one country to another or from one union to another within the same country, there are some commonalities. These include establishing general ethical and professional standards that members must adhere to.